Explorative study regarding influenza vaccine hesitancy among HIV-infected patients - Valentina Marchese; Samuele Storti; Claudia Morganti; Giorgio Tiecco; Melania Degli Antoni; Emanuele Focà; Francesco Castelli; Eugenia Quiros-Roldan (Taylor & Francis Group, 2022)
There are scarce data regarding influenza vaccination among people with HIV infection (PWHIV). The goal of this explorative study is to assess hesitancy toward influenza vaccination in a group of PWHIV during the COVID-19 pandemic. A questionnaire was administered to 219 patients vaccinated at our clinic during the 2020-2021 campaign. It evaluated subjects' adherence to influenza vaccine over the last three seasonal vaccination campaigns, vaccine confidence, complacency and convenience, and the effect of the pandemic on the choice to become vaccinated. The population was divided into two groups: fully adherent to influenza vaccine (all three campaigns, 117 patients) and non-fully adherent (one or two campaigns, 102 patients). Adherence increased in the non-fully adherent group in 2020-2021, but the pandemic did not affect the choice. Misbeliefs emerged: the influenza vaccine was considered protective against SARS-CoV-2 (22.8% of the total population); almost half of all patients thought the influenza vaccine could improve their CD4 T cell level (57.3% in fully adherent, 40.2% in non-fully adherent, p < .05). In 2020-2021 campaign, three quarters of the non-fully adherent group would not have been vaccinated in a location other than our clinic (75.5% vs. 88.9% in the fully adherent group, p < .05). Conclusively, offering a secure and private space for vaccination against influenza seems to encourage vaccination; healthcare professionals should improve counseling to increase adherence and correct misbeliefs.